The Ile13 residue of microcin J25 is essential for recognition by the receptor FhuA, but not by the inner membrane transporter SbmA - Socias, Sergio Benjamin (2009)
Entry of the peptide antibiotic microcin J25 (MccJ25) into target cells is mediated by the outer membrane receptor FhuA and the inner membrane protein SbmA. The latter also transports MccB17 into the cell cytoplasm. Comparison of MccJ25 and MccB17 revealed a tetrapeptide sequence (VGIG) common to both antibiotics. We speculated that this structural feature in MccJ25 could be a motif recognized by SbmA. To test this hypothesis, we used a MccJ25 variant in which the isoleucine in VGIG (position 13 in the MccJ25 sequence) was replaced by lysine (I13K). In experiments in which the FhuA receptor was bypassed, the substituted microcin showed an inhibitory activity similar to that of the wild-type peptide. Moreover, MccJ25 interfered with colicin M uptake by FhuA in a competition assay, while the I13K mutant did not. From these results, we propose that the Ile13 residue is only required for interaction with FhuA, and that VGIG is not a major recognition element by SbmA. © 2009 Federation of European Microbiological Societies.